(untitled) - FREEMAN, M. HERBERT; HANNA, J. MARSHALL \ KAHN, GILBERT (USA, 1968)
1.Payroll Accounting / 2.Computation of Earnings / 3.Payroll Recors and Procedures / 4.Payroll Tax Returns / 5.Notes payable and notes receivable / 6.Promissory Notes / 7.Notes Payable / 8.Notes Receivable / 9.Depreciation and bad debts / 10.Depreciation / 11.Bad Debts / 12.Accruals and Deferrals / 13.Accruel Expenses / 14.Accrued and Deferred Income / 15.Completion of the Accounting Cycle / 16.Making End - of - Period Adjustments / 17.Combination Journal and / 18.Journalless - Ledgerless Bookkeeping / 19.The Combination Journal / 20.Direct - Entry Records for Purchases / 21.Direct - Entry Records for Sales
Incluye indice analitico pag.443
Keywords: CONTABILIDAD